2015
DOI: 10.1055/s-0034-1398373
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Patellofemoral Dislocation: Risk Factors for Recurrent Instability

Abstract: Patellofemoral instability is a complex problem, which can be difficult to manage. The purpose of this study was to describe the demographics of patients with a first-time patellofemoral dislocation, and identify risk factors for recurrent instability. This was a single institution, institutional review board-approved, retrospective review of >2,000 patients with a patellar dislocation between 1998 and 2010. Inclusion criteria are as follows: (1) no prior history of patellofemoral subluxation or dislocation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
161
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 17 publications
5
161
0
7
Order By: Relevance
“…large-scale population studies have identified prior patellar dislocation, 3 younger age, [2][3][4][5][6] female sex, 5 participation in athletic activities, [2][3][4]6 soft-tissue laxity/disruption, 6 and anthropometric measures 6 as risk factors for patellar dislocation. Additional anatomic and radiographic risk factors associated with patellofemoral joint instability include abnormal bony anatomy 2,7 (e.g., patella alta, trochlear dysplasia, increased tibial tubercle-trochlear groove distance, and patellar tilt) and soft-tissue factors 6 (e.g., medial retinaculum laxity, medial patellofemoral ligament disruption, and weakened vastus medialis).…”
mentioning
confidence: 99%
“…large-scale population studies have identified prior patellar dislocation, 3 younger age, [2][3][4][5][6] female sex, 5 participation in athletic activities, [2][3][4]6 soft-tissue laxity/disruption, 6 and anthropometric measures 6 as risk factors for patellar dislocation. Additional anatomic and radiographic risk factors associated with patellofemoral joint instability include abnormal bony anatomy 2,7 (e.g., patella alta, trochlear dysplasia, increased tibial tubercle-trochlear groove distance, and patellar tilt) and soft-tissue factors 6 (e.g., medial retinaculum laxity, medial patellofemoral ligament disruption, and weakened vastus medialis).…”
mentioning
confidence: 99%
“…25,28 However, some authors have noted that sex is not a significant risk factor for patellar dislocation, and that in the case of acute, traumatic patellar dislocation, males actually have a greater incidence of injury. 21,47 …”
Section: Discussionmentioning
confidence: 99%
“…The post-traumatic marrow edema is usually seen in the femoral condyle in 80-100% of patients, while in 41-61% of patients it is detectable even at the level of the inferior-medial aspect of the patella. Osteochondral lesions are more common on the patellar (70%) rather than in femoral (40%) articular surface, and can result in intra-articular loose bodies in 1/3 of patients [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Traumatic Mechanismmentioning
confidence: 99%